Roles of protein arginine methyltransferase 1 (PRMT1) in brain development and disease - Hashimoto, Misuzu; Fukamizu, Akiyoshi; Nakagawa, Tsutomu; Kizuka, Yasuhiko (Biochimica et biophysica acta. General subjects, 2021)
Protein arginine methyltransferase 1 (PRMT1), a major type I arginine methyltransferase in mammals, methylates histone and non-histone proteins to regulate various cellular functions such as transcription, DNA damage response, and signal transduction. This review summarizes previous and recent studies on PRMT1 functions in major cell types of the central nervous system. We also discuss the potential involvement of PRMT1 in neurodegenerative diseases such as amyotrophic lateral sclerosis and frontotemporal dementia. Also, we raise key questions that must be addressed in the future to more precisely understand the roles of PRMT1. Recent studies revealed that PRMT1 is essential for the development of neurons, astrocytes, and oligodendrocytes, although further investigation using cell type-specific PRMT1-deficient animals is required. In addition, the relevance of PRMT1 in neurodegenerative diseases will continue to be a hot topic. PRMT1 is important for neural development and neurodegenerative diseases. •PRMT1 catalyzes asymmetric dimethylation of arginine residues of proteins.•PRMT1 in neural stem cells is essential for early brain development.•Arginine methylation by PRMT1 and 5 are indispensable for myelination.•Methylation reduces phase separation of neurodegeneration-causative factors.•Methyl-arginine-specific antibodies and chemical tools accelerate PRMT study.